Competencies of Physical Education Teachers and Their Influence on Student Learning Outcomes in Elementary School - Ikhwan Abduh; Andi Saparia; Jumain Jumain (Musamus Journal of Physical Education and Sport (MJPES), 2023)
Objective. The better student learning outcomes will influence the student's ability to solve problems that will be faced in real life after completing education and teachers play a very important role in helping students achieve this. In this research, it will carry an investigation out regarding teacher pedagogical competence and its influence on student learning outcomes. Materials and methods. The research carried out was quantitative survey type research with the entire population as a sample, namely 35 teachers in 2 sub-districts in Palu City. The instrument used was a questionnaire and data collection techniques used interview and observation techniques and distributed questionnaires. Data analysis was carried out by conducting a t-test. Results. The research results found a t-test value of 75.971 with a significance level of 0.000 < α0.05, this shows that there is a significant influence between the variables studied. Conclusion. The conclusion of this research was that there was an influence of teacher pedagogic competence on student learning outcomes. The results can be used for teachers to develop professionalism by prioritizing pedagogical competence as the focus of development.